2018
DOI: 10.1021/acs.est.7b05479
|View full text |Cite
|
Sign up to set email alerts
|

Nano-TiO2-Catalyzed Dehydrochlorination of 1,1,2,2-Tetrachloroethane: Roles of Crystalline Phase and Exposed Facets

Abstract: Nanoscale titanium dioxide ( nTiO) is one of the most widely used metal oxide nanomaterials. Once released into the environment, nTiO may catalyze abiotic transformation of contaminants and consequently affect their fate and effects. Here, we show that the overall catalytic efficiency of nTiO for the dehydrochlorination reaction of 1,1,2,2-tetrachloroethane, a commonly used solvent, depends on the crystalline phase and exposed facets of nTiO, which significantly affect the adsorption capacity and surface catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…63 Generally, the NH 3 -TPD profiles of the materials (Figure 4c) are divided into two sections covering 100−300 and 300−800 °C, respectively, corresponding to NH 3 desorbed from the relatively weak and strong acidic sites. 24,64 [Considering that the amount of Brønsted acid sites on the surfaces of the hematite materials was negligible (Figure 4b), the intensity profiles in NH 3 -TPDwhich typically quantifies the total densities of Lewis and Brønsted acid sites 65 essentially represent the concentrations of the Lewis acid sites.] In general, Hem_100 possessed higher densities of Lewis acid sites, especially those with stronger acidity, than Hem_001, corroborating its higher catalytic activity (i.e., k r value).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Generally, the NH 3 -TPD profiles of the materials (Figure 4c) are divided into two sections covering 100−300 and 300−800 °C, respectively, corresponding to NH 3 desorbed from the relatively weak and strong acidic sites. 24,64 [Considering that the amount of Brønsted acid sites on the surfaces of the hematite materials was negligible (Figure 4b), the intensity profiles in NH 3 -TPDwhich typically quantifies the total densities of Lewis and Brønsted acid sites 65 essentially represent the concentrations of the Lewis acid sites.] In general, Hem_100 possessed higher densities of Lewis acid sites, especially those with stronger acidity, than Hem_001, corroborating its higher catalytic activity (i.e., k r value).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the previous studies (mostly conducted using bulk materials) on metal oxides-catalyzed hydrolysis of organic contaminants, metal atoms on the surface of metal oxides, such as ferric iron (Fe­(III)) atoms, have been proposed to be the reactive sites. For instance, Fang et al recently proposed that Fe­(III) atoms as a Lewis acid can coordinate with ester O atom in organophosphorus flame retardants, which partially stabilizes the alkoxide intermediate and promotes the cleavage of the ester bond, thus enhancing the hydrolysis reaction. Note that the abundance and activity of surface reactive moieties of metal oxides can be significantly influenced by their intrinsic properties (e.g., crystal phases and exposed facets). However, only a few studies have discussed how the key physicochemical properties of iron (hydr)­oxide nanoparticles (e.g., mineral phase, crystalline phase, and particle size) can affect their efficiency in modulating hydrolysis reactions. ,, For instance, it was reported that iron (hydr)­oxides of different mineral phases (e.g., α-Fe 2 O 3 , α-FeOOH, and γ-FeOOH) enhance the hydrolysis of organophosphorus compounds to different extents, possibly due to the different coordination environments of Fe­(III) atoms within the crystal structures. , To date, the potential effects of exposed facets on the catalytic efficiencies of iron (hydr)­oxide nanoparticles for hydrolysis reactions of organic contaminants have not been illustrated. It is important to note that naturally occurring nanocrystalline iron (hydr)­oxides may be exposed with different facets, depending on their crystal phases and morphologies, ,,, and engineered iron (hydr)­oxide nanocrystals are often designed to possess specific facets for enhanced reactivity/selectivity. , (In fact, facet-dependent adsorption by hematite, , goethite, , and lepidocrocite has been reported before.)…”
Section: Introductionmentioning
confidence: 99%
“…For assessing the relative surface hydrophobicity of NMs, the contact angles of DI water and simulated body fluids on thin-films of NMs using the sessile drop method , and the n -dodecane–water partition coefficients ( K DW ) of NMs , were measured in triplicate at room temperature (25 °C ± 1 °C). The thin films of NMs were prepared by filtering the NM suspensions through 0.05 μm Nuclepore Track-Etched membranes (Whatman, England).…”
Section: Methodsmentioning
confidence: 99%
“…14,27,31−33 It has been proposed that the reactions between water molecules and metal oxides in the first hydration shell are dictated by the atomic structures of different crystal facets, 34−36 which are key factors affecting the hydrophobic interaction and ligand exchange during physical and chemical adsorption processes, respectively. As a result, a number of crystalline metal oxides have exemplified facet-dependent affinity toward various compounds, including heavy metals, 14,37 organic pollutants, 31,38 humic substances, 27,39 and proteins. 32,40 This research aims at exploring the mechanisms governing the facet-dependent binding of NOM on both engineered and naturally occurring nanoscale metal oxides, with an emphasis on the selectivity of different crystal facets for the diverse components of NOM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous research has revealed that binding between NOM molecules and nanoparticulate metal oxides was largely determined by the physicochemical properties of nanocrystals, such as size and surface charge. ,, Recent experimental evidence and theoretical calculations pointed to the important role of an intrinsic property of nanocrystals, an exposed facet, in determining the binding affinity of metal oxides. ,, It has been proposed that the reactions between water molecules and metal oxides in the first hydration shell are dictated by the atomic structures of different crystal facets, which are key factors affecting the hydrophobic interaction and ligand exchange during physical and chemical adsorption processes, respectively. As a result, a number of crystalline metal oxides have exemplified facet-dependent affinity toward various compounds, including heavy metals, , organic pollutants, , humic substances, , and proteins. , …”
Section: Introductionmentioning
confidence: 99%